Analysis of engine performance with NGV - Sulaiman, Nabila; Ihsan, Sany Izan; Mohiuddin, A. K. M.; Mel, Maizirwan (2011)
This paper presents experimental results carried out to evaluate brake thermal efficiency and fuel consumption by gasoline and compressed natural gas (CNG). In this experiment, a 4-cylinders gasoline engine has been modified to bi-fuel engine, then the engine is operated for the condition of fixed load condition to obtain same brake power output from both fuels and all the corresponding results such as fuel flow rate and brake thermal efficiency have been measured for evaluation. The test results show that gasoline has higher fuel consumption and brake thermal efficiency than CNG. Details results including fuel consumption and brake thermal efficiency have been discussed in this paper.